Optic neuropathy in late-onset neurodegenerative Chédiak–Higashi syndrome. Issue 5 (25th August 2015) - Desai, Ninad; Weisfeld-Adams, James D; Brodie, Scott E; Cho, Catherine; Curcio, Christine A; Lublin, Fred; Rucker, Janet C
Abstract : Background: The classic form of Chédiak–Higashi syndrome (CHS), an autosomal recessive disorder of lysosomal trafficking with childhood onset caused by mutations in LYST, is typified ophthalmologically by ocular albinism with vision loss attributed to foveal hypoplasia or nystagmus. Optic nerve involvement and ophthalmological manifestations of the late-onset neurodegenerative form of CHS are rarely reported and poorly detailed. Methods: Case series detailing ophthalmological and neurological findings in three adult siblings with the late-onset form of CHS. Results: All three affected siblings lacked features of ocular albinism and demonstrated significant optic nerve involvement as evidenced by loss of colour and contrast vision, central visual field loss, optic nerve pallor, retinal nerve fibre layer thinning by optical coherence tomography (OCT) and abnormal visual evoked potential, with severity corresponding linearly to age of the sibling and severity of neurological disease. Further, unusual prominence of a 'third line' on macular OCT that may be due to abnormal melanosomes was seen in all three siblings and in their father. Neurological involvement included parkinsonism, cerebellar ataxia and spastic paraparesis. Conclusions: This report expands the ophthalmological phenotype of the late-onset neurodegenerative form of CHS to include optic neuropathy with progressive vision loss, even in the absence of ocular albinism, and abnormal prominence of the interdigitation zone between cone outer segment tips and apical processes of retinal pigment epithelium cells on macular OCT.